TEH MAWAR NAIK KELAS : INTEGRASI INOVASI KEMASAN DAN SOCIAL COMMERCE DALAM PEMBERDAYAAN KWT - Elly Antika; Hariyono Rakhmad; Ery Setiyawan Jullev Atmadji; Nanik Anita Mukhlishoh; Enik Rukiati (Universitas Merdeka Madiun, 2026)
The Nawasena Women Farmer Group (KWT) in Karangpring Village, Sukorambi District, Jember Regency has developed tea and syrup products made from red rose flowers as an effort to increase the added value of local commodities. However, product marketing remains limited to local exhibitions due to packaging that has yet to meet modern marketing standards and the absence of nutritional information that could strengthen consumer confidence. This community service program aims to enhance product competitiveness through quality validation, packaging innovation, and digital marketing reinforcement. Activities carried out included laboratory analysis of vitamin C content, vitamin A, total flavonoids, and antioxidant activity; packaging redesign with a food safety approach and professional image; tea bag production training; and digital marketing assistance through TikTok and Instagram. Laboratory test results revealed a vitamin C content of 29.50 mg/100 g, vitamin A of 12.00 g/100 g, total flavonoids of 3.72 mg GAE/g extract, and antioxidant activity of 57.50%, confirming the character of rose tea as a functional food product. Packaging innovation improved hygiene, product protection, and visual appeal, while digital marketing training expanded the potential market reach through e-commerce channels. This intervention demonstrates that the integration of product quality improvement, packaging professionalization, and the utilization of digital marketing is capable of optimizing the added value and commercialization opportunities of Nawasena KWT's processed rose products in a sustainable manner.